1989
DOI: 10.1002/jgt.3190130603
|View full text |Cite
|
Sign up to set email alerts
|

Maximally connected digraphs

Abstract: This paper introduces a new parameter / = / ( G ) for a loopless digraph G, which can be thought of as a generalization of the girth of a graph. Let K, A, 6, and D denote respectively the connectivity, arc-connectivity, minimum degree, and diameter of G. Then it is proved that A = 6 if D s 21 and K = 6 if D I 21 -1. Analogous results involving upper bounds for K and A are given for the more general class of digraphs with loops. Sufficient conditions for a digraph to be super-A and super-rc are also given. As a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(108 citation statements)
references
References 11 publications
(9 reference statements)
1
84
0
Order By: Relevance
“…Indeed their underlying digraphs are generalized de Bruijn (resp Kautz) digraphs whose connectivity is known. Therefore using the results of [8,12] we get: As we will see the hyperarc connectivity of the generalized de Bruijn and Kautz dihypergraphs is equal to their minimum degree as soon as s ≥ 2. The result was more difficult to prove.…”
Section: Connectivity Of De Bruijn and Kautz Dihypergraphsmentioning
confidence: 88%
“…Indeed their underlying digraphs are generalized de Bruijn (resp Kautz) digraphs whose connectivity is known. Therefore using the results of [8,12] we get: As we will see the hyperarc connectivity of the generalized de Bruijn and Kautz dihypergraphs is equal to their minimum degree as soon as s ≥ 2. The result was more difficult to prove.…”
Section: Connectivity Of De Bruijn and Kautz Dihypergraphsmentioning
confidence: 88%
“…D12: [FaFi89,FiFaEs90] For a given digraph G = (V, E) with diameter D, the semigirth, denoted`(G), is the greatest integer`between 1 and D such that for any u, v 2 V , (a) if dist(u, v) <`, the shortest u-v directed walk is unique and there are no u-v directed walks of length dist(u, v) + 1.…”
Section: Definitionsmentioning
confidence: 99%
“…Since then it has been found that many well-known graphs are super connected or super edge-connected. In particular, Soneoka [10] showed that the de Bruijn digraph B(d, n) is super edge-connected for any d ≥ 2 and n ≥ 1; Fábrega and Fiol [5] proved that the Kautz digraph K(d, n) is super edge-connected for any d ≥ 3 and n ≥ 2.…”
Section: κ(G) ≤ λ(G) ≤ δ(G) Where δ(G) Is the Minimum Degree Of G Amentioning
confidence: 99%